Exploring the Relationship between Students’ Attitudes, Language Learning Strategies, Exposure, and Grammatical Competence in English Language Acquisition - Balones, Jerlyn G; Gempes, Gloria P (Top Linguistic and Language Journal (TLLJ), 2023)
This study investigated the relationship between students’ attitudes, language learning strategies, exposure, and grammatical competence in English language acquisition among university students in emerging countries. The study aimed to identify the correlation and combined and singular influence of these variables and to determine the best-fit model for grammatical competence.A total of 400 respondents were identified through proportional percentage sampling, and quantitative-causal method was used for data collection. The data were analyzed using Product-Moment correlation, multiple-linear regression, and Structural Equation Modeling (SEM) to ensure the integrity and rigor of the research. The results showed that students had high levels of study attitude and language learning strategies, moderate levels of language exposure, and high levels of grammatical competence. There was a significant relationship among attitude, language learning strategy, and exposure to grammatical competence, but no singular influence among the variables was found. The best-fit model indicated that grammatical competence was strongly influenced by language learning strategy and exposure.The findings of this study are significant as they provide insights into the interplay of students’ attitudes, language learning strategies, exposure, and grammatical competence in English language acquisition. The study also contributes to the pool of knowledge by examining all four variables in a single study. This research is particularly relevant for language teachers and policy-makers who are interested in improving the English language proficiency of university students in emerging countries.In conclusion, this study highlights the importance of language learning strategies and exposure in developing grammatical competence in English language acquisition. It also emphasizes the need to consider students’ attitudes towards language as a background variable in language performance studies. The study’s findings have implications for language teaching and policy-making, and future research can build on these findings to develop effective language teaching strategies for university students in emerging countries.